2015
DOI: 10.3928/1081597x-20150820-06
|View full text |Cite
|
Sign up to set email alerts
|

Opaque Bubble Layer Risk Factors in Femtosecond Laser-assisted LASIK

Abstract: This study confirms the already known OBL risk factors with a larger cohort and suggests for the first time that an elevated corneal hysteresis is an independent predictive risk for OBL occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 18 publications
(25 reference statements)
1
19
1
Order By: Relevance
“…8,21 Kunert et al 9 demonstrated a decrease in the surface regularity index in femtosecond lenticule extraction accompanying an increase in pulse energy (150, 180, and 195 nJ), which also supported this conclusion. Moreover, the temporary accumulation of gas bubbles in the intrastromal interface creates transient opacity, or opaque bubble layer, which sometimes diffuses into the corneal stroma, subconjunctival space, and anterior chamber, 4,22 and further interferes with the subsequent procedures in SMILE, such as femtosecond laser photodisruption pulses and lenticule separation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,21 Kunert et al 9 demonstrated a decrease in the surface regularity index in femtosecond lenticule extraction accompanying an increase in pulse energy (150, 180, and 195 nJ), which also supported this conclusion. Moreover, the temporary accumulation of gas bubbles in the intrastromal interface creates transient opacity, or opaque bubble layer, which sometimes diffuses into the corneal stroma, subconjunctival space, and anterior chamber, 4,22 and further interferes with the subsequent procedures in SMILE, such as femtosecond laser photodisruption pulses and lenticule separation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The energy needed to cause this reaction has been the focus of significant study. [3][4][5][6] The functional parameters of femtosecond lasers, such as the repetition rate of the laser system, energy, and spot-track-distance, significantly affect the interaction of the laser with the corneal tissue. De Medeiros et al 7 reported that femtosecond laser energy level had an effect on corneal stromal cell death and inflammation in a rabbit model.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…OBL occurs when these bubbles expand and become trapped in the anterior stroma, at the interface plane ( 1 , 42 ). The incidence of OBL ranges up to 48% ( 42 , 43 ), its formation being influenced by flap diameter under 8 mm ( 44 ), thick corneas ( 43 , 45 ), high hysteresis ( 43 , 45 ) and laser settings such as: spot spacing, pocket size and energy level ( 42 ). Severe OBL presence can interfere with interface dissection ( 42 ) and can disturb eye tracking of the excimer laser ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Complications limited to femtosecond laser use are epithelial gas breakthrough [18] and opaque bubble layer (OBL) formation [1,59]. A vertical gas breakthrough occurs between the dissection plane and the subepithelial space, resulting in an escape of gas bubbles into the subepithelial space [60].…”
Section: Risk Of Intraoperative Complications Associated With Flap Creationmentioning
confidence: 99%